Ameliorative effect of vitamin C against hepatotoxicity induced by emamectin benzoate in rats. (July 2017) - Khaldoun Oularbi, H; Richeval, C; Lebaili, N; Zerrouki-Daoudi, N; Baha, M; Djennas, N; Allorge, D
In the present study, we aimed to assess the potential protective effect of ascorbic acid (AA) against emamectin benzoate (EMB)-induced hepatotoxicity. For this purpose, biochemical, histopathological and analytical investigations were performed. Male Wistar rats were distributed into three groups, that is, a control group, an EMB group given 10 mg EMB/kg body weight (BW) by gavage and an EMB + AA group given 10 mg EMB/kg BW and vitamin C intraperitoneally (200 mg/kg). The duration of the treatment was 28 days and the duration of the study was 42 days. There was a statistically significant increase of all hepatic biomarkers, that is, aspartate aminotransferase, alanine aminotransferase and gamma-glutamyltransferase activities, and glycemia, in EMB-treated group when compared with the control group. Light microscopic observations revealed variable signs of hepatotoxicity in the EMB group, which were represented by alteration of normal hepatic architecture, inflammatory cell infiltration, hepatocellular steatosis and foci of necrosis at 28 and 42 days post -treatment. However, co-treatment with vitamin C reduced EMB-related liver toxicity and diminished the abnormal biochemical and architectural damage. Emamectin B1a and B1b residues were detectable in all plasma samples of treated rats at 14, 21 and 28 days of treatment. The drug liver tissue concentration was significantly lower in EMB + AA group compared with EMB group at 28 and 42 days. In conclusion, the findings of the present study clearly indicate a significant protective action of vitamin C against EMB hepatotoxicity.